Case Report: Nonsurgical management of painless cervical motor radiculopathy - Lee, Yong Ho (Frontiers in Rehabilitation Sciences, 2025)
BackgroundPainless motor radiculopathy is a rare clinical entity, accounting for approximately 5%–8% of cervical radiculopathy cases. While current guidelines recommend early surgical intervention for patients with severe motor deficits, the efficacy of nonsurgical management remains unclear.Case presentationWe present a case of a 67-year-old man with sudden onset of right shoulder motor paralysis [Medical Research Council (MRC) grade 3-] without pain. MRI revealed multilevel foraminal stenosis at C5–C7–T1 and central disc protrusion at C4–5, without cord compression. The patient elected nonsurgical management and received four epidural steroid injections (two interlaminar and two transforaminal) over five weeks. Motor function progressively improved, reaching MRC grade 5-, and shoulder range of motion was fully restored. No adverse effects occurred.ConclusionThis case demonstrates that epidural steroid injections can be an effective alternative to surgery for selected patients with painless cervical motor radiculopathy and severe motor dysfunction. Individualized treatment strategies should be considered, and further research is warranted to establish optimal management approaches.